Association between gut microbiota and peptic ulcer disease, particularly gastric ulcer and duodenal ulcer: a two-sample Mendelian randomization study - Dong, Zhenhua; Yu, Kai; Xin, Yuchao; Gao, Xulei; Bu, Fan; Zhao, Dingliang; Ren, Donghui; Lu, Ji; Wang, Daguang (Frontiers in Microbiology, 2024)
Background: Recent an observational study has suggested a potential connection between gut microbiota (GM) and peptic ulcer diseases, particularly gastric ulcer (GU) and duodenal ulcer (DU). But the causal connection remains unsure. Methods: A two-sample mendelian randomization (MR) is carried out to explore the connection between the GM and DU or GU. Data on the GM comes from the MiBioGend database and GU or DU data is based on the FinnGen database. One group of single nucleotide polymorphisms (SNPs) (p<5 × 10 -8 ) are served as instrumental variables (IVs). To obtain a more comprehensive conclusion, the other which SNPs (p<1 × 10 -5 ) are selected as IVs. Inverse variance weighting (IVW) is used to determine causal relationship. Results: At the level of p<1 × 10 -5 , the IVW analysis suggests that Clostridiaceae1, Butyriccoccus and Peptcoccus have harmful effects on GU, while LachnospiraceaeUCG004 and MollicutesRF9 have beneficial effects on GU. Next about DU, the IVW analysis suggested that Lentisphaeria, Negativicutes, Clostridiaceae1, Clostridi-umseMnsustricto1, ErysipelotrichaceaeUCG003, LachnospiraceaeNC2004group, Selenomonadale, Victivallales,Lentisphaerae have harmful effects, while Catenibacterium, Escherichia.Shigella, Lachnospirace-aeUCG008, Sutterella have beneficial effects. when p<5 × 10 -8 , IVW analysis suggests that GM has no significant influence on GU or DU. Conclusion: This two-sample MR indicates a causal relationship between GM and GU or DU.